2019
DOI: 10.1007/s42452-019-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcination temperature on characterization of natural hydroxyapatite prepared from carp fish bones

Abstract: Hydroxyapatite is one of the most common bio-ceramic materials which is currently used in the biomedical field. The development of hydroxyapatite is due to their crystallographic and chemical similarity to the hard tissue of human body. The present study aims to prepare hydroxyapatite from a bio-waste material (carp fish bone) as an ecofriendly and inexpensive source by calcination treatment. The calcination process was applied at various calcining temperatures; the heating rate was kept constant at 10 °C min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 17 publications
(17 reference statements)
5
22
0
1
Order By: Relevance
“…SEM micrographs of the NP showed that this mineral had a heterogeneous microstructure and is mainly composed of particles of irregular geometries in the agglomerated form. 47 SEM images of the 10CsCl/NP-800 illustrate that the surface morphology of the prepared catalyst become more compact and dense in which the catalyst particles adopt a morphology of blocks. Moreover, the catalyst particles tend to agglomerate aer being impregnated with CsCl because cesium covers all the pores and surface of the NP, resulting in a very dense and highly agglomerated microstructure.…”
Section: P Nmr Masmentioning
confidence: 99%
“…SEM micrographs of the NP showed that this mineral had a heterogeneous microstructure and is mainly composed of particles of irregular geometries in the agglomerated form. 47 SEM images of the 10CsCl/NP-800 illustrate that the surface morphology of the prepared catalyst become more compact and dense in which the catalyst particles adopt a morphology of blocks. Moreover, the catalyst particles tend to agglomerate aer being impregnated with CsCl because cesium covers all the pores and surface of the NP, resulting in a very dense and highly agglomerated microstructure.…”
Section: P Nmr Masmentioning
confidence: 99%
“…41 The FTIR bands of 3572 cm −1 and 632 cm −1 are associated with hydroxyl group (O-H). 19,42 The peaks of phosphate ions belonging to 1030-1100, 962, 603, 569, and 473 cm −1 were detected which are almost same as. 43 The bands usually appeared in the range of 3440-3412 cm −1 are representative of water molecule, 44 these peaks were identified in all of our samples.…”
Section: Resultsmentioning
confidence: 63%
“…These peaks, which are shown by black arrows for S 8 sample (continuous: main peaks and dash: weak peaks) in Figure 2C, are in agreement with previous research. 19,[32][33][34][35] Reyes-Gasga and Becerril 35 extracted HA from human permanent molar teeth by heat treatment at different temperatures. The authors similarly found the TCP peaks at higher temperatures (1000°C and 1200°C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations